Autonomy, the Right Not to Know, and the Right to Know Personal Research Results: What Rights are There, and Who Should Decide about Exceptions?. Issue 1 (2014) - Helgesson, Gert
Abstract : Bioethicists have for quite some time discussed the right to know and the right not to know personal health information, such as genetic information acquired in health care and incidental health-related findings in research. Several international ethical guidelines explicitly defend these rights. My own interest in these matters stems from my participation in ethics-related research tied to a longitudinal screening study on Type I diabetes involving young children. A few of the participating parents (about 2 percent) did not want to be informed if the study revealed their child had a high risk of developing diabetes. This response was troublesome, not least since the information would concern the child's and not the parents' health. Our inclination was that there cannot be a right not to know that should be granted without qualifications. Furthermore, other contextual factors, e.g., that parents experienced pressure to participate and felt concern about some of the personal data handled in the study, gave reason to question whether autonomous decisions were made regarding participation. The autonomy of their expressed desire not to know was therefore questionable.